Interventions preventing ankle sprains; previous injury and high-risk sport participation as predictors of compliance - Janssen, K. W.; van der Zwaard, B. C.; Finch, C. F.; van Mechelen, W.; Verhagen, E. A. L. M. (Journal of Science and Medicine in Sport, 2016)
Objectives: To describe the association between participants` person-related potential predictor variables and cumulative compliance with interventions for preventing ankle sprains: neuromuscular training, wearing an ankle brace, and a combined training and bracing. Design: Secondary analysis of compliance data from a randomized controlled trial (RCT) comparing measures preventing ankle ligament injuries. Methods: Ordinal regression with a backward selection method was used to obtain a descriptive statistical model linking participants` person-related potential predictor variables with the monthly cumulative compliance measurements for three interventions preventing ankle ligament injuries. Results: Having had a previous ankle injury was significantly associated with a higher compliance with all of the preventive measures trialed. Overall compliance with bracing and the combined intervention was significantly lower than the compliance with NM training. Per group analysis found that participating in a high-risk sport, like soccer, basketball, and volleyball, was significantly associated with a higher compliance with bracing, or a combined bracing and NM training. In contrast, participating in a high-risk sport was significantly associated with a lower per group compliance with NM training. Conclusions: Future studies should include at least registration of previous ankle sprains, sport participation (high- or low-risk), experience in NM training, and hours of sport exposure as possible predictors of compliance with interventions preventing ankle sprains. Practitioners should take into account these variables when prescribing preventive neuromuscular training or bracing.